2022
DOI: 10.1038/s41419-022-05276-9
|View full text |Cite
|
Sign up to set email alerts
|

GSDME deficiency leads to the aggravation of UVB-induced skin inflammation through enhancing recruitment and activation of neutrophils

Abstract: Gasdermin E (GSDME)-mediated pyroptosis is induced in keratinocytes of UVB-challenged skin. The role of GSDME in UVB-caused skin damage remains unknown. To explore the role of GSDME in UVB-induced skin inflammation. We compared differences in skin appearance, histological features, keratinocyte death modalities, infiltration of immune cells, and levels of some inflammatory cytokines between Gsdme−/− mice and wild type (WT) mice after UVB exposure. We explored whether keratinocytes contribute to GSDME deficienc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
13
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 21 publications
(19 citation statements)
references
References 37 publications
2
13
0
Order By: Relevance
“…Similar observations were first made by Chen et al [22]. The same team extended their research and found later that after UVB radiation exposure, different cell deaths in the mice's epidermis occurred at the same time, namely GSDME-mediated pyroptosis, apoptosis and necroptosis [23], which confirms the diverse nature of GSDME we mentioned in the introduction. GSDME has also been reported to play a role as a mediator in the sustained chronic inflammatory skin condition in zebra fish [24].…”
Section: Discussionsupporting
confidence: 84%
“…Similar observations were first made by Chen et al [22]. The same team extended their research and found later that after UVB radiation exposure, different cell deaths in the mice's epidermis occurred at the same time, namely GSDME-mediated pyroptosis, apoptosis and necroptosis [23], which confirms the diverse nature of GSDME we mentioned in the introduction. GSDME has also been reported to play a role as a mediator in the sustained chronic inflammatory skin condition in zebra fish [24].…”
Section: Discussionsupporting
confidence: 84%
“…And GSDME de ciency leads to the aggravation of UVB-induced skin in ammation through enhancing recruitment and activation of neutrophils. We also analyzed the correlations between IL6 expression and immune cell in ltration ratio and found that important molecular markers for UVB-treated are related to the ratio of Neutrophils (Chen et al, 2022). Of course, we cannot rule out the error of the CIBERSORT algorithm in calculating, but our work promotes the study of the immune response in skin after UVB irradiation.…”
Section: Discussionmentioning
confidence: 92%
“…Microarray technology has been widely used to investigate a variety of biological systems, thanks to the rapid development of computer science, and technology is being used in an increasing number of studies to investigate immunology and the pathophysiology of in ammatory diseases (Karasinska et al, 2020; Villaseñor-Park & Ortega-Loayza, 2013; Zhang et al, 2022).To avoid the false-positive rates of independent microarray analysis data, we combined two microarray data sets from Gene Expression Omnibus (GEO) and batchnormalized it for analysis to identify key genes between the control group and the UVB-treated group. the examination of gene expression pro les is considered an essential process to explore the functional elements of the genome and understand the associations between hazardous factors and induced molecular mechanisms.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, GSDME-modulated pyroptosis may play a vital role in chemotherapy-induced nephrotoxicity. Moreover, loss of GSDME also aggravated skin damage in UVB-treated mice by promoting the infiltration and activation of neutrophils [ 61 ]. Previous studies have identified NOD1 as a key player in host-microbial defense and multiple inflammatory diseases.…”
Section: Discussionmentioning
confidence: 99%